The Impact of Russian-Ukraine Conflict on Profitability and Valuation of Indonesian Coal Stocks - Erman Sumirat; Dzikri Firmansyah Hakam; Irfan Sihab Budin F (Journal of Economics and Business UBS, 2023)
This research investigates the impact of the 2022 Russian invasion of Ukraine on the profitability and valuation of publicly listed Indonesian coal companies. Leveraging panel regression, the study offers empirically grounded perspectives on how an acute geopolitical conflict disrupted global energy trade flows to influence key financial metrics of a major exported commodity. Specifically, the analysis focuses on five leading Indonesian coal miners over 2019-2022. Profitability dynamics are examined through gross profit margins while valuations reliance on price-to-earnings ratios. Control variables capture coal prices, a conflict indicator, inflation, interest rates, and exchange rate fluctuations. Results reveal the global coal price spike had a statistically significant positive impact on profit margins, affirming the turmoil's commodity super-cycle upside. However, valuations diverged from earnings trends, suggesting more complex reassessments of long-term prospects. The conflict itself directly affected profitability but not valuations. This research contributes timely empirical insights on an understudied intersection of geopolitics, commodity markets, and emerging market equities. Evidence-based quantification of financial linkages and risk transmission inform both theory and practice. Strategic decision makers obtain granular clarity regarding exposures and opportunities during energy market turmoil.